‘Aisyiyah information system management training in Makassar City - Arni Arni; Sitti Rahmawati Arfah; Nuryanti Mustari; Sabriani Sabriani; Andita Mudiyawati (Community Empowerment, 2024)
This training aims to increase the capacity of 'Aisyiyah cadres in utilizing information technology to support the activities of the 'Aisyiyah organization. The method used in PKM is carried out in three stages, preparation by socializing activities to the community, implementation is carried out by means of training, and evaluation is carried out by distributing pre-test and post-test questionnaires to measure the level of knowledge and skills of partners . The results of this service show that there has been an increase in partners' knowledge and skills regarding 'Aisyiyah Makassar City information system management training with a percentage of 95%. This shows that there are differences in the level of knowledge after being given training in managing the 'Aisyiyah information system which is increasing.